Undergraduate Curriculum to Teach and Provide Research Skills on Hardware Design for SDR Applications in FPGA Technology - Torres Gomez, Jorge; Jerez Naranjo, Yannelys; Dressler, Falko; Fernandez-Getino Garcia, M. Julia (IEEE access, 2021)
Software Defined Radio (SDR) technologies play today an important role in modern wireless networks due to their flexibility to implement re-configurable hardware designs. In light of the importance to operate and develop such technologies, academic programs in the communications engineering field demand an introduction to Digital Signal Processing (DSP) and SDR communication schemes accordingly. Typically, the teaching of this subject is afforded through projects and hands-on activities in classrooms. However, provided their relevance in the current state-of-the-art, this topic also provides a framework to teach soft skills concerning research abilities in students. This paper introduces an academic program to the development of SDR functionality as well as research skills based on exposure to state-of-the-art research. Through projects, hands-on activities are conducted to teach digital signal processing designs using Field Programmable Gate Array (FPGA) technology. The course aims to develop technical skills to implement communication system blocks. Besides, workshops and seminars are prepared to support the development of research and communication skills. The proposed course is flexible to incorporate on a given academic program as an elective subject to further support topics related to communication theory and discrete-time signals. Learning outcomes are designed to develop enhanced technical skills in SDR design and simultaneously a critical discussion of the devised solutions in light of the state-of-the-art. Also, skills related to identifying, formulating, and discussing engineering problems are further reinforced. Results from supported projects developed in the classroom exhibit completed assignments superior to 90% of participant students. Learning objectives concerning the technical skills were successfully covered (90%) in comparison to research and communicating skills (80%). Additionally, research skills and the ability to disseminate knowledge gradually improved in seminars. Finally, results of the current course exhibit improvements of 25% regarding the acquired skills in digital signal processing in comparison to previous courses.